Catalytic performance in citral hydrogenation and characterization of PtSn catalysts supported on activated carbon felt and powder - Vilella, Irene María Julieta (2005)
The liquid phase citral hydrogenation carried out at 70 °C and atmospheric pressure over Pt and PtSn catalysts supported on both activated carbon powder (C) and felt (ACf), was investigated. It was found that the addition of Sn to the Pt catalysts increases the reaction rate of the citral hydrogenation, this influence being more important for carbon-based catalysts. Besides, the Sn addition sharply enhances the selectivity to double unsaturated alcohols (nerol and geraniol) for both catalyst series. The secondary products were the unsaturated aldehyde (citronellal), the single-unsaturated alcohol (citronellol) and the cyclization products (isopulegol and menthol). The performance of these catalysts in the citral hydrogenation was related with the characteristics of the metallic phase, which were determined by test reactions of the metallic phase (cyclohexane dehydrogenation and cyclopentane hydrogenolysis), H2 chemisorption, TPR and XPS in order to postulate the models of the metallic surface. In this sense, a fraction of ionic Sn (detected by XPS) would be deposited near Pt aggregates, thus enhancing the polarization of the carbonyl group of the citral molecule, and leading to an increase in the selectivity to nerol and geraniol. This effect appears to be different depending on the support type.